Proyek Pembangunan Jembatan Rumah Susun Padat Karya “Pengamatan Pelaksanaan Pekerjaan Plat pada Jembatan Rumah Susun Padat Karya” - A Riduan Umar; Pio Ranap Tua Naibaho (NUCLEUS, 2022)
This study aims to determine the consideration factors for the selection of the erection girder method, an effective method for the implementation of the erection girder, the factors that affect the erection girder implementation process, and a comparison of the implementation of the erection girder using a crawler crane and a launcher girder. First, both primary and secondary data were collected, then an analysis of the crawler crane and launcher girder methods was carried out. In each method, an analysis of material and tool requirements, time, cost, and quality of work is carried out. Furthermore, the results of the analysis are used to determine the most appropriate method. Based on the analysis that has been carried out, it can be ascertained that the factors that are considered in the use of the girder erection method include field conditions, location location, weather conditions, human resources, and specifications of tools and equipment. The basic difference between the crawler crane and launcher girder methods is the way the girder beam is placed at the fulcrum. The crawler crane method has a relatively faster processing time compared to the launcher girder method because the mobilization of tools is carried out in separate conditions, while the launcher girder method has advantages in terms of cost, tool precision, and operation method. From the analysis calculation, it is found that the effective method for erection girder work on underpass sta: 99 + 910 Trans Sumatra toll road project using crawler crane.